Progress in Theoretical Investigation on Oxide Layer Structure Over Metallic Plutonium - XIE Liu-hua; QIU Rui-zhi (He huaxue yu fangshe huaxue, 2023)
The oxide layer structure over plutonium is the central issue of plutonium corrosion science. In this paper we review our progress in theoretical investigation on the oxide layer structure of plutonium. First of all, our first-principles calculations combined with chemical thermodynamics shows that plutonium monoxide is unstable under ambient pressure and probably decompose into plutonium sesquioxide and metallic plutonium. However, it could be stabilized under pressure and the stabilization mechanism is illustrated by the electronic structure calculations. Secondly, based on the quasirandom structure model, the first-principles calculations show that monoxide could also be stabilized by the carbon. The anomalous variation of lattice parameter of oxycarbide is reproduced by our theoretical studies and the microscopic origin is revealed. Finally, using analogous structures of lanthanide intermediate oxide, we show that homogeneous PunO2n-2 between PuO2 and Pu2O3 are energetically favorable. Thus, a ladder-like layer structure(Pu/PuOxCy/Pu2O3/PunO2n-2/PuO2) is proposed to improve a simple sandwich-like model of the oxide layer over metallic plutonium. This model provides theoretical guidance for the research on the plutonium corrosion.